2017
DOI: 10.1530/joe-16-0424
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone regulated genes in cerebral cortex development

Abstract: The physiological and developmental effects of thyroid hormones are mainly due to the control of gene expression after interaction of T 3 with the nuclear receptors. To understand the role of thyroid hormones on cerebral cortex development, knowledge of the genes regulated by T 3 during specific stages of development is required. In our laboratory, we previously identified genes regulated by T 3 in primary cerebrocortical cells in culture. By comparing these data with transcriptomics of purified cell types fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 99 publications
2
103
0
4
Order By: Relevance
“…The hypothesis of fetal programing by maternal thyroid dysfunction via disturbed early fetal brain development and later onset of neurodevelopmental disorders appears biologically plausible, which was one of the well-known viewpoints of Sir Bradford Hill in the evaluation of a causal relationship (59 experimental studies have demonstrated developmental structural and/or functional defects after exposure to maternal thyroid dysfunction in pregnancy that may overlap with the developmental abnormalities described in neurodevelopmental disorders, and identified genes involved in the brain development that are regulated by T3 (37). Results from human observational studies are intriguing to interpret, and further studies are needed to determine and support other viewpoints of causality e.g.…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis of fetal programing by maternal thyroid dysfunction via disturbed early fetal brain development and later onset of neurodevelopmental disorders appears biologically plausible, which was one of the well-known viewpoints of Sir Bradford Hill in the evaluation of a causal relationship (59 experimental studies have demonstrated developmental structural and/or functional defects after exposure to maternal thyroid dysfunction in pregnancy that may overlap with the developmental abnormalities described in neurodevelopmental disorders, and identified genes involved in the brain development that are regulated by T3 (37). Results from human observational studies are intriguing to interpret, and further studies are needed to determine and support other viewpoints of causality e.g.…”
Section: Perspectivesmentioning
confidence: 99%
“…Brain development is a highly regulated process and an important part of this regulation includes the coordinated and timely expression of many different genes. Thyroid hormones are important developmental factors and their crucial role in early brain development is facilitated via the regulation of gene expression (37). T3 binds to nuclear thyroid hormone receptors, and recent in vitro studies have identified genes of primary cerebrocortical cells that are regulated transcriptionally by T3 (38,39).…”
Section: Thyroid Hormones and Brain Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian studies, also fT4 and fT3 have been detected before the initial thyroid activity, as well as early deyodinase activity and TR synthesis in CNS cells [16]. TRα1 has been localized in all CNS regions, while TRβ1 has been found selectively in the hypothalamus, the pituitary, the retina, and the cochlea, but only in later stages [17, 18].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Тирео-идные гормоны стимулируют пролиферацию и диф-ференцировку клеток мозга, экспрессию факторов роста, синтез белков внеклеточного матрикса и т. п. [12,16,17]. Поэтому изучение механизмов тиреоид-ассоциированных депрессий представляет собой актуальную задачу биологии и медицины.…”
Section: обсуждение полученных результатовunclassified